Fabrication of keratin-cellulose cryogel for agricultural application - Kwek, Vanessa Keem Shin (Nanyang Technological University, 2020)
Human hair keratin is often exploited for biomedical applications due to its abundance in nature, toughness, bioactivity and biodegradability. Pure keratin, however, lacks mechanical integrity, and this inevitably limits its use. Therefore, the main aims are to strengthen the mechanical integrity of pure keratin by adding cellulose as a reinforcement via possible secondary interactions between cellulose and keratin and to explore their potential use in agriculture such as being a hydroponic substrate. Water uptake ratio and porosity of the composite keratin cryogel fabricated is comparable to commercial ones (i.e., Oasis Cube) at 47.64 g/g and 51.28 % respectively. Fourier transform infrared spectroscopy (FTIR) shows a stark difference from pure keratin in the region around wavelength of 1000-1200 cm-1 indicating the presence of cellulose while scanning electron microscopy (SEM) clearly shows the difference: interconnected porous structure of keratin-cellulose with thick, fibrous walls of cellulose present. Mechanical properties are enhanced when cellulose is added and further increased when various nanoparticles being as micronutrients are introduced. Compressive moduli of the keratin-cellulose cryogel is 3 times higher than the pure keratin cryogel. The feasibility and effectiveness of these cryogels as hydroponic substrate (solid growth medium) are further tested where mung beans are grown on the cryogels with commercial oasis cube as a control. These findings demonstrated the feasibility of producing human hair keratin-cellulose cryogels, with tunable porosity and mechanical properties, which have supported the healthy growth of plants, suggesting their potential for agricultural application in hydroponics.